Improvement of Response Time by Running Games on a Cloud Gaming System with Layer Vatcher and Movement Prediction - Sadaike, Marcelo T.; Gutiérrez, José C.; Valiente, Rodolfo; Bressan, Graça (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
With the growing video games industry, new markets and technologies are emerging. Electronic games of the new generation are increasingly requiring more processing and powerful video cards. The solution that is gaining more prominence is Cloud Gaming, which the player performs a command, the information is sent and processed remotely on a cloud, then the images return as a video stream back to the player using the Internet. To improve the Quality of Experience (QoE), it is proposed a model that reduces the response time between the player command and the stream of the resulting game scenes through a framework called Cloud Manager. The game must be encoded in different layers so that the Cloud Manager can use layer caching techniques, in the background, and future state prediction using a prediction matrix, in the character layer, in order to reduce the network bandwidth usage, bitrate transmission and network latencies. To validate the results, an action game with god-view as point of view is used in a Cloud Gaming system called Uniquitous.